2009
DOI: 10.1038/hr.2009.94
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with uncontrolled hypertension and cardiovascular risk in hypertensive 60-year-old men and women—a population-based study

Abstract: The objective of this study was to describe cardiovascular risk profiles of 60-year-olds with uncontrolled diagnosed hypertension (X140/90 mm Hg) in comparison with individuals with controlled diagnosed hypertension. To study how medical, lifestyle and socioeconomic factors are associated with uncontrolled diagnosed hypertension in men and women separately, a populationbased, cross-sectional study of 4228 60-year-olds in Sweden, of whom 503 men and 445 women had previously diagnosed hypertension, was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Warfarin is generally considered to be under-prescribed in AF patients [35], and was prescribed in about half of the patients AF patients in the present study, which is in line with what is common in other Western countries [17]. The findings of the present study can possibly be extrapolated to pharmacotherapies in other patient groups as well, such as those with hypertension and dyslipidemia [32, 36], although this was not the scope of the present study. In fact, some of our results were more salient after adjustments for co-morbidities.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Warfarin is generally considered to be under-prescribed in AF patients [35], and was prescribed in about half of the patients AF patients in the present study, which is in line with what is common in other Western countries [17]. The findings of the present study can possibly be extrapolated to pharmacotherapies in other patient groups as well, such as those with hypertension and dyslipidemia [32, 36], although this was not the scope of the present study. In fact, some of our results were more salient after adjustments for co-morbidities.…”
Section: Discussionsupporting
confidence: 85%
“…Individuals in neighborhoods with low socio-economic status, despite the relatively low annual fee, are however likely to have small financial margins [31], and may refrain from seeking healthcare because of the cost. Men who refrained from health care because of the costs have been shown to more often have uncontrolled diagnosed hypertension [32], and it is possible that similar group of individuals are more common in neighborhoods with low SES, and have fewer recommended pharmacotherapies prescribed when diagnosed with AF. Aspirin is not considered to be effective in preventing stroke in high risk groups, such as patients with AF [12].…”
Section: Discussionmentioning
confidence: 99%
“…A Swedish population-based study in hypertensive 60-year-old persons with and without diabetes by Carlsson et al found an inverse, direct association of high waist circumference with uncontrolled hypertension [40]. The same seems to be true for patients in primary care irrespective of diabetes status [41].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, living in an apartment instead of a house (as an indicator of lower socio-economic status) remained a significantly protective factor in an adjusted model in women (OR = 0.55, 95%CI 0.35-0.85). The authors stated that the finding was puzzling and offered no explanation [40]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation